Low-carbon environment-friendly refractory castable based on nano-sol and preparation process of low-carbon environment-friendly refractory castable

The combination of composite aerogel powder prepared by nano-sol and modified nano-silica sol solves the problem of insufficient thermal shock stability of refractory castables under high temperature and complex working conditions, achieves excellent thermal insulation and mechanical properties at high temperature, and extends service life.

CN120943657APending Publication Date: 2025-11-14CHANGXING YUNFENG CHARGE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511484480.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-17
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing refractory castables have insufficient thermal shock stability under high-temperature and complex working conditions, resulting in short service life and failing to meet the requirements of modern industrial large-scale and harsh environments.

Method used

Based on nanosol, a low-carbon and environmentally friendly refractory castable is prepared by combining composite aerogel powder and modified nanosilica sol. The porous structure of ZrO2 hollow microspheres and halloysite is used to enhance thermal insulation and support. Combined with KH-570 modification, the bonding strength of each component is improved, and mullite whiskers are formed to enhance high-temperature stability.

Benefits of technology

It significantly improves the thermal insulation and mechanical properties of refractory castables, reduces structural deformation at high temperatures, extends service life, and improves thermal shock resistance and flexural strength retention.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120943657A_ABST
    Figure CN120943657A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of refractory materials, and particularly provides a nano-sol-based low-carbon environment-friendly refractory castable and a preparation process thereof, and the nano-sol-based low-carbon environment-friendly refractory castable comprises composite aerogel powder, modified nano-silica sol, compact corundum, brown corundum, white corundum, alumina, silicon carbide, activated alumina and spherical asphalt. The low-carbon environment-friendly refractory castable based on the nano sol has the advantages of being low in carbon, environmentally friendly, excellent in heat insulation performance, high in thermal shock resistance and high in mechanical strength, and is suitable for high-temperature industries such as metallurgy and building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of refractory materials technology, and in particular relates to a low-carbon and environmentally friendly refractory castable based on nano-sol and its preparation process. Background Technology

[0002] Refractory castables, as important monolithic refractory materials, possess advantages such as variable shape, simple manufacturing process, and high temperature resistance, and are widely used in many industrial fields such as metallurgy, building materials, and power. With the rapid development of modern industrial technology, various industries are placing increasingly stringent requirements on the performance of refractory materials.

[0003] Traditional refractory castables face several challenges in their preparation and use: the production process often consumes significant amounts of energy, and their low strength and insufficient erosion resistance result in short service lives and frequent replacements, increasing costs and impacting production efficiency. Compared to traditional refractory castables, Al₂O₃-SiC-C castables exhibit higher strength, better thermal shock resistance, and superior wear and erosion resistance. However, with the development of modern processes and technological innovations, manufacturing is becoming increasingly large-scale, placing greater demands on the application environments of Al₂O₃-SiC-C castables. These environments require not only high-temperature resistance but also greater resistance to slag erosion, making the application environment and standards more stringent. Therefore, there is an urgent need to develop a new type of refractory castable with excellent thermal shock resistance and a long service life.

[0004] Patent application CN105218113A discloses a silica sol-bonded corundum castable and its preparation method. This technology modifies the silica sol in situ by introducing a silane coupling agent, forming an organic / inorganic hybrid structure. This results in good flow properties, accelerates the formation of the silica sol network structure, facilitates subsequent demolding, and provides high early strength. The production process is simple, but it lacks improvement in thermal shock stability and high-temperature durability, limiting the application of samples under complex high-temperature conditions. Additionally, patent application CN118324499A discloses a thermally insulating refractory castable and its preparation method. This castable incorporates modified chopped basalt fibers. The modified chopped basalt fibers contain hydroxyl groups, which improve the wettability of the material and water, and enhance the strength of the thermally insulating refractory castable. However, its thermal shock stability is insufficient, failing to meet the needs of long-term industrial production. Summary of the Invention

[0005] To address the aforementioned issues and further improve the mechanical properties and thermal shock resistance of refractory castables, this application provides a low-carbon, environmentally friendly refractory castable based on nano-sol and its preparation process.

[0006] This application first provides a low-carbon, environmentally friendly refractory castable based on nano-sol, using the following technical solution: A low-carbon and environmentally friendly refractory castable based on nano-sol includes the following components: composite aerogel powder, modified nano-silica sol, dense corundum, brown corundum, white corundum, bauxite, silicon carbide, activated alumina, and spherical asphalt. The composite aerogel powder is made from SiO2, halloysite, and ZrO2 hollow microspheres.

[0007] Furthermore, the preparation method of the composite aerogel powder includes the following steps: Tetraethyl orthosilicate and citric acid were dispersed evenly in anhydrous ethanol, then deionized water was added, the mixture was heated and stirred, halloysite and ZrO2 hollow microspheres were added, and after stirring evenly, ammonia water was added dropwise. The mixture was then sealed and allowed to stand to form a composite gel. Discard the upper layer of the composite gel, add anhydrous ethanol for aging, freeze-dry the composite gel after aging, grind and sieve it, and collect the sieve material to obtain the composite aerogel powder.

[0008] Furthermore, the mass ratio of the ZrO2 hollow microspheres to halloysite is (0-2):1.

[0009] Furthermore, the preparation method of the ZrO2 hollow microspheres includes the following steps: Sucrose was dispersed in deionized water, and after hydrothermal reaction, the precipitate was collected, washed, and dried under vacuum. The precipitate was then added to hydrogen peroxide for reaction, and the precipitate was collected, washed, and dried under vacuum to obtain carbon sphere templates. Carbon sphere templates and zirconium oxychloride octahydrate were dispersed in deionized water, and then ammonia solution was added dropwise to adjust the pH. The reaction was stirred, the precipitate was collected, washed, dried under vacuum, calcined at high temperature, and cooled to obtain ZrO2 hollow microspheres.

[0010] Furthermore, when adjusting the pH by adding the ammonia solution, the pH range is 5-5.5.

[0011] Furthermore, the preparation method of the modified nano-silica sol includes the following steps: KH-570 was dispersed in anhydrous ethanol to obtain a KH-570 solution; after the silica sol and deionized water were mixed evenly, the KH-570 solution was added and the mixture was heated to react, thus obtaining the modified nano silica sol.

[0012] This application also provides a preparation process for a low-carbon and environmentally friendly refractory castable based on nano-sol, comprising the following steps: Weigh out composite aerogel powder, dense corundum, brown corundum, white corundum, bauxite, silicon carbide, activated alumina, and spherical asphalt. Mix and stir, then add modified nano silica sol and deionized water, and wet mix to obtain a mixed slurry. The mixed slurry is injected into a mold to form a shape, cured in the mold, and then demolded to obtain a blank. The billet is dried and then calcined at high temperature to obtain a low-carbon and environmentally friendly refractory castable based on nano-sol.

[0013] Furthermore, the mixing and stirring process involves premixing for 60-100 seconds followed by dry mixing for 45-60 seconds.

[0014] Furthermore, the curing time for the mold is 24-72 hours.

[0015] Furthermore, the high-temperature calcination involves heating to 1000℃-1200℃ at a rate of 3℃ / min and holding for 2-4 hours, followed by heating to 1500℃-1900℃ at a rate of 5℃ / min and holding for 2-4 hours.

[0016] Compared with the prior art, this application has the following beneficial effects: 1. The composite aerogel powder contained in the low-carbon and environmentally friendly refractory castable based on nanosol prepared in this application has the advantage of high porosity, which can significantly block the heat conduction path; and the ZrO2 hollow microspheres added to the composite aerogel powder not only enhance the heat insulation effect with their hollow structure, but also provide internal support for the porous network of aerogel with their own excellent rigidity, making up for the shortcomings of insufficient rigidity of aerogel, avoiding the deterioration of the mechanical properties of the castable due to the introduction of aerogel, and achieving a balance between heat insulation performance and mechanical properties.

[0017] 2. The modified nano-silica sol in the low-carbon and environmentally friendly refractory castable prepared in this application incorporates KH-570, which helps the SiO2 component and active alumina component in the composite aerogel powder to combine, promotes the formation of mullite whiskers during subsequent high-temperature calcination, fills the internal pores, strengthens the tight bond between the components, and reduces the possibility of cracking. The introduction of KH-570 effectively improves the strength of the sample, reduces structural deformation and strength decay at high temperatures, and enables the castable to maintain good stability under high-temperature conditions.

[0018] 3. The composite aerogel powder in the low-carbon and environmentally friendly refractory castable based on nanosol prepared in this application has excellent buffering capacity. When the castable faces severe temperature fluctuations, the porous structure of the aerogel can reduce the volume change caused by thermal expansion and contraction, and reduce the internal thermal stress level. At the same time, the porous structure of the aerogel, the hollow structure of the ZrO2 hollow microspheres, and the tubular structure of halloysite can effectively inhibit the initiation and propagation of microcracks, significantly improve the thermal shock resistance of the castable, reduce the risk of breakage, and extend the service life of the refractory castable. Attached Figure Description

[0019] Figure 1 This is a TEM image of the ZrO2 hollow microspheres from Example 1 of this application.

[0020] Figure 2 This is a TEM image of the SiO2 and halloysite portions in the composite aerogel powder of Example 1 of this application. Detailed Implementation

[0021] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.

[0023] When using “including,” “having,” and “contains” as described herein, the intention is to cover non-exclusive inclusion, unless an explicit qualifying term such as “only,” “consisting of,” etc., is used, in which case another component may be added.

[0024] The terms "preferred," "more preferably," "better," and "even better" used in this application refer to embodiments of this application that provide certain beneficial effects under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the description of one or more preferred embodiments does not imply that other embodiments are unavailable, nor is it intended to exclude other embodiments from the scope of this application. That is, in this application, "preferred," "more preferably," "better," and "even better" are merely descriptions of implementations or embodiments with better effects, but do not constitute a limitation on the scope of protection of this application.

[0025] In this application, terms such as "further," "even more," and "particularly" are used for descriptive purposes and indicate differences in content, but should not be construed as limiting the scope of protection of this application.

[0026] In this application, "at least one" means one or more, such as one, two, or more. "Multiple" or "several" means at least two, such as two, three, etc., and "multi-layered" means at least two layers, such as two layers, three layers, etc., unless otherwise explicitly specified. In the description of this application, "several" means at least one, such as one, two, etc., unless otherwise explicitly specified.

[0027] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0028] Unless otherwise specified, all steps in this application may be performed sequentially or randomly. For example, the method comprising steps (a) and (b) indicates that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order; for example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc. Unless otherwise stated, singular terms may include plural forms and should not be construed as having a quantity of one.

[0029] In this application, "above" or "below" includes the number itself. For example, "below 1" includes 1.

[0030] In this application, room temperature refers to 0~40℃, including but not limited to 10~40℃, or further to 20~30℃.

[0031] The present application will be further illustrated by the following examples, but these examples do not limit the scope of the present application.

[0032] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in this application, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. All reagents or instruments whose manufacturers are not specified are conventional products that can be purchased commercially. In addition to the specific methods, equipment, and materials used in the embodiments, based on the knowledge of the prior art possessed by one of ordinary skill in the art and the description in this application, any prior art methods, equipment, and materials similar to or equivalent to those described, used, or made by the methods, equipment, and materials in the embodiments of this application may be used to implement this application.

[0033] Example 1 The low-carbon and environmentally friendly refractory castable based on nano-sol in this embodiment is composed of the following components: composite aerogel powder, modified nano-silica sol, dense corundum, brown corundum, white corundum, bauxite, silicon carbide, activated alumina, and spherical asphalt.

[0034] The preparation method of ZrO2 hollow microspheres in this embodiment includes the following steps: 60g of sucrose was dispersed in 500mL of deionized water and hydrothermally reacted at 170℃ for 8 hours. After naturally cooling to room temperature, the precipitate was collected, washed successively with deionized water and anhydrous ethanol, dried at 80℃, and then added to 50mL of hydrogen peroxide. The mixture was stirred at 60℃ for 2 hours, filtered, and the precipitate was collected. It was washed with deionized water until neutral and then vacuum dried at 80℃ to obtain carbon sphere templates. 50g of carbon sphere template and 25g of zirconium oxychloride octahydrate were dispersed in 500mL of deionized water. Then, a 1mol / L ammonia solution was slowly added dropwise to adjust the pH to 5.0. The reaction was continued with stirring for 2 hours. The precipitate was collected by centrifugation, washed with anhydrous ethanol until neutral, dried under vacuum at 80℃, and then heated to 300℃ at a rate of 3℃ / min and held for 1 hour in air. The temperature was then increased to 600℃ at a rate of 5℃ / min and held for 4 hours. After naturally cooling to room temperature, ZrO2 hollow microspheres were obtained.

[0035] The preparation method of the composite aerogel powder in this embodiment includes the following steps: 300 mL of tetraethyl orthosilicate and 30 mL of 0.05 mol / L citric acid were dispersed in 500 mL of anhydrous ethanol. 120 mL of deionized water was added dropwise while stirring. After stirring at 40 °C for 2 hours, 40 g of halloysite and 20 g of ZrO2 hollow microspheres were added. After ultrasonic stirring until homogeneous, ammonia was added dropwise at a rate of 1 drop / second until the pH reached 8.0. The mixture was then sealed and allowed to stand at 40 °C for 6 hours to form a composite gel. Discard the upper layer of the composite gel, add anhydrous ethanol, age at 30°C for 24 hours, replace the anhydrous ethanol every 8 hours, then freeze-dry the composite gel, grind it through a 100-mesh sieve, and collect the sieve material to obtain the composite aerogel powder.

[0036] The preparation method of the modified nano-silica sol in this embodiment includes the following steps: Weigh 50g of KH-570 and dissolve it in 500mL of anhydrous ethanol. Stir well to obtain KH-570 solution. After mixing 5 kg of silica sol and 5 kg of deionized water evenly, add KH-570 solution and heat to 50℃ and stir for 2 hours to obtain modified nano silica sol.

[0037] The preparation method of the low-carbon and environmentally friendly refractory castable based on nano-sol in this embodiment includes the following steps: Weigh out 0.8 kg of composite aerogel powder, 1.2 kg of dense corundum (composed of 0.6 kg of dense corundum with a particle size of 5-8 mm and 0.6 kg of dense corundum with a particle size of 3-5 mm), 2.2 kg of brown corundum (composed of 1.1 kg of brown corundum with a particle size of 1-3 mm and 1.1 kg of brown corundum with a particle size of 0-1 mm), 1.4 kg of white corundum with a particle size of 325 mesh, and 1.8 kg of bauxite (composed of 1.1 kg of bauxite with a particle size of 3-5 mm). The mixture consists of m and 0.7 kg of bauxite with a particle size of 1-3 mm, 1.3 kg of silicon carbide (composed of 0.7 kg of silicon carbide with a particle size of 1-3 mm and 0.6 kg of silicon carbide with a particle size of 325 mesh), 0.8 kg of activated alumina, and 0.5 kg of spherical asphalt. It is premixed for 100 seconds, then dry-mixed for 60 seconds, followed by the addition of 1.2 kg of modified nano-silica sol and 0.5 kg of deionized water, and wet-mixed for 180 seconds to obtain a mixed slurry. The mixed slurry is injected into a mold, vibrated to form the shape, and cured in the mold at 25°C for 48 hours before demolding to obtain the blank. The billet is dried at 110℃ for 24 hours, then heated to 1100℃ at a rate of 3℃ / min and held for 3 hours in air, and then heated to 1650℃ at a rate of 5℃ / min and held for 3 hours to obtain a low-carbon and environmentally friendly refractory castable based on nano-sol.

[0038] Example 2 The low-carbon and environmentally friendly refractory castable based on nano-sol in this embodiment is composed of the following components: composite aerogel powder, modified nano-silica sol, dense corundum, brown corundum, white corundum, bauxite, silicon carbide, activated alumina, and spherical asphalt.

[0039] The preparation method of ZrO2 hollow microspheres in this embodiment includes the following steps: 60g of sucrose was dispersed in 500mL of deionized water and hydrothermally reacted at 170℃ for 8 hours. After naturally cooling to room temperature, the precipitate was collected, washed successively with deionized water and anhydrous ethanol, dried at 80℃, and then added to 50mL of hydrogen peroxide. The mixture was stirred at 60℃ for 2 hours, filtered, and the precipitate was collected. It was washed with deionized water until neutral and then vacuum dried at 80℃ to obtain carbon sphere templates. 50g of carbon sphere template and 25g of zirconium oxychloride octahydrate were dispersed in 500mL of deionized water. Then, a 1mol / L ammonia solution was slowly added dropwise to adjust the pH to 5.5. The reaction was continued with stirring for 2 hours. The precipitate was collected by centrifugation, washed with anhydrous ethanol until neutral, dried under vacuum at 80℃, and then heated to 300℃ at a rate of 3℃ / min and held for 1 hour in air. The temperature was then increased to 600℃ at a rate of 5℃ / min and held for 4 hours. After naturally cooling to room temperature, ZrO2 hollow microspheres were obtained.

[0040] The preparation method of the composite aerogel powder in this embodiment includes the following steps: 300 mL of tetraethyl orthosilicate and 30 mL of 0.05 mol / L citric acid were dispersed in 500 mL of anhydrous ethanol. 120 mL of deionized water was added dropwise while stirring. After stirring at 40 °C for 2 hours, 30 g of halloysite and 30 g of ZrO2 hollow microspheres were added. After ultrasonic stirring until homogeneous, ammonia was added dropwise at a rate of 1 drop / second until the pH reached 8.0. The mixture was then sealed and allowed to stand at 40 °C for 6 hours to form a composite gel. Discard the upper layer of the composite gel, add anhydrous ethanol, age at 30°C for 24 hours, replace the anhydrous ethanol every 8 hours, then freeze-dry the composite gel, grind it through a 100-mesh sieve, and collect the sieve material to obtain the composite aerogel powder.

[0041] The preparation method of the modified nano-silica sol in this embodiment includes the following steps: Weigh 50g of KH-570 and dissolve it in 500mL of anhydrous ethanol. Stir well to obtain KH-570 solution. After mixing 5 kg of silica sol and 5 kg of deionized water evenly, add KH-570 solution and heat to 50℃ and stir for 2 hours to obtain modified nano silica sol.

[0042] The preparation method of the low-carbon and environmentally friendly refractory castable based on nano-sol in this embodiment includes the following steps: Weigh out 0.5 kg of composite aerogel powder, 1.2 kg of dense corundum (composed of 0.6 kg of dense corundum with a particle size of 5-8 mm and 0.6 kg of dense corundum with a particle size of 3-5 mm), 2.2 kg of brown corundum (composed of 1.1 kg of brown corundum with a particle size of 1-3 mm and 1.1 kg of brown corundum with a particle size of 0-1 mm), 1.4 kg of white corundum with a particle size of 325 mesh, and 1.8 kg of bauxite (composed of 1.1 kg of bauxite with a particle size of 3-5 mm). The mixture consists of m and 0.7 kg of bauxite with a particle size of 1-3 mm, 1.3 kg of silicon carbide (composed of 0.7 kg of silicon carbide with a particle size of 1-3 mm and 0.6 kg of silicon carbide with a particle size of 325 mesh), 0.5 kg of activated alumina, and 0.5 kg of spherical asphalt. It is premixed for 60 seconds, then dry-mixed for 45 seconds, followed by the addition of 1.2 kg of modified nano-silica sol and 0.5 kg of deionized water, and wet-mixed for 180 seconds to obtain a mixed slurry. The mixed slurry is injected into a mold, vibrated to form the shape, and cured in the mold at 25°C for 24 hours before being demolded to obtain the blank. The billet is dried at 110℃ for 24 hours, then heated to 1000℃ at a rate of 3℃ / min and held for 2 hours in air, and then heated to 1500℃ at a rate of 5℃ / min and held for 2 hours to obtain a low-carbon and environmentally friendly refractory castable based on nano-sol.

[0043] Example 3 The low-carbon and environmentally friendly refractory castable based on nano-sol in this embodiment is composed of the following components: composite aerogel powder, modified nano-silica sol, dense corundum, brown corundum, white corundum, bauxite, silicon carbide, activated alumina, and spherical asphalt.

[0044] The preparation method of ZrO2 hollow microspheres in this embodiment includes the following steps: 60g of sucrose was dispersed in 500mL of deionized water and hydrothermally reacted at 170℃ for 8 hours. After naturally cooling to room temperature, the precipitate was collected, washed successively with deionized water and anhydrous ethanol, dried at 80℃, and then added to 50mL of hydrogen peroxide. The mixture was stirred at 60℃ for 2 hours, filtered, and the precipitate was collected. It was washed with deionized water until neutral and then vacuum dried at 80℃ to obtain carbon sphere templates. 50g of carbon sphere template and 25g of zirconium oxychloride octahydrate were dispersed in 500mL of deionized water. Then, a 1mol / L ammonia solution was slowly added dropwise to adjust the pH to 5.0. The reaction was continued with stirring for 2 hours. The precipitate was collected by centrifugation, washed with anhydrous ethanol until neutral, dried under vacuum at 80℃, and then heated to 300℃ at a rate of 3℃ / min and held for 1 hour in air. The temperature was then increased to 600℃ at a rate of 5℃ / min and held for 4 hours. After naturally cooling to room temperature, ZrO2 hollow microspheres were obtained.

[0045] The preparation method of the composite aerogel powder in this embodiment includes the following steps: 300 mL of tetraethyl orthosilicate and 30 mL of 0.05 mol / L citric acid were dispersed in 500 mL of anhydrous ethanol. 120 mL of deionized water was added dropwise while stirring. After stirring at 40 °C for 2 hours, 20 g of halloysite and 40 g of ZrO2 hollow microspheres were added. After ultrasonic stirring until homogeneous, ammonia was added dropwise at a rate of 1 drop / second until the pH reached 8.0. The mixture was then sealed and allowed to stand at 40 °C for 6 hours to form a composite gel. Discard the upper layer of the composite gel, add anhydrous ethanol, age at 30°C for 24 hours, replace the anhydrous ethanol every 8 hours, then freeze-dry the composite gel, grind it through a 100-mesh sieve, and collect the sieve material to obtain the composite aerogel powder.

[0046] The preparation method of the modified nano-silica sol in this embodiment includes the following steps: Weigh 50g of KH-570 and dissolve it in 500mL of anhydrous ethanol. Stir well to obtain KH-570 solution. After mixing 5 kg of silica sol and 5 kg of deionized water evenly, add KH-570 solution and heat to 50℃ and stir for 2 hours to obtain modified nano silica sol.

[0047] The preparation method of the low-carbon and environmentally friendly refractory castable based on nano-sol in this embodiment includes the following steps: Weigh out 1.0 kg of composite aerogel powder, 1.2 kg of dense corundum (composed of 0.6 kg of dense corundum with a particle size of 5-8 mm and 0.6 kg of dense corundum with a particle size of 3-5 mm), 2.2 kg of brown corundum (composed of 1.1 kg of brown corundum with a particle size of 1-3 mm and 1.1 kg of brown corundum with a particle size of 0-1 mm), 1.4 kg of white corundum with a particle size of 325 mesh, and 1.8 kg of bauxite (composed of 1.1 kg of bauxite with a particle size of 3-5 mm). The mixture consists of m and 0.7 kg of bauxite with a particle size of 1-3 mm, 1.3 kg of silicon carbide (composed of 0.7 kg of silicon carbide with a particle size of 1-3 mm and 0.6 kg of silicon carbide with a particle size of 325 mesh), 1.0 kg of activated alumina, and 0.5 kg of spherical asphalt. It is premixed for 60 seconds, then dry-mixed for 45 seconds, followed by the addition of 1.2 kg of modified nano-silica sol and 0.5 kg of deionized water, and wet-mixed for 180 seconds to obtain a mixed slurry. The mixed slurry is injected into a mold, vibrated to form the shape, and cured in the mold at 25°C for 72 hours before being demolded to obtain the blank. The billet is dried at 110℃ for 24 hours, then heated to 1200℃ at a rate of 3℃ / min and held for 4 hours in air, and then heated to 1900℃ at a rate of 5℃ / min and held for 4 hours to obtain a low-carbon and environmentally friendly refractory castable based on nano-sol.

[0048] Control group 1 The low-carbon, environmentally friendly refractory castable based on nano-sol in this control group consists of the following components: composite aerogel powder, modified nano-silica sol, dense corundum, brown corundum, white corundum, bauxite, silicon carbide, activated alumina, and spherical asphalt.

[0049] The preparation method of the composite aerogel powder in this control group includes the following steps: 300 mL of tetraethyl orthosilicate and 30 mL of 0.05 mol / L citric acid were dispersed in 500 mL of anhydrous ethanol. 120 mL of deionized water was added dropwise while stirring. After stirring at 40 °C for 2 hours, 60 g of halloysite was added. After ultrasonic stirring until homogeneous, ammonia was added dropwise at a rate of 1 drop / second until the pH reached 8.0. The mixture was then sealed and allowed to stand at 40 °C for 6 hours to form a composite gel. Discard the upper layer of the composite gel, add anhydrous ethanol, age at 30°C for 24 hours, replace the anhydrous ethanol every 8 hours, then freeze-dry the composite gel, grind it through a 100-mesh sieve, and collect the sieve material to obtain the composite aerogel powder.

[0050] The preparation method of the low-carbon and environmentally friendly refractory castable based on nano-sol in this control group includes the following steps: Weigh out 0.8 kg of composite aerogel powder, 1.2 kg of dense corundum (composed of 0.6 kg of dense corundum with a particle size of 5-8 mm and 0.6 kg of dense corundum with a particle size of 3-5 mm), 2.2 kg of brown corundum (composed of 1.1 kg of brown corundum with a particle size of 1-3 mm and 1.1 kg of brown corundum with a particle size of 0-1 mm), 1.4 kg of white corundum with a particle size of 325 mesh, and 1.8 kg of bauxite (composed of 1.1 kg of bauxite with a particle size of 3-5 mm). The mixture consists of m and 0.7 kg of bauxite with a particle size of 1-3 mm, 1.3 kg of silicon carbide (composed of 0.7 kg of silicon carbide with a particle size of 1-3 mm and 0.6 kg of silicon carbide with a particle size of 325 mesh), 0.8 kg of activated alumina, and 0.5 kg of spherical asphalt. It is premixed for 100 seconds, then dry-mixed for 60 seconds, followed by the addition of 1.2 kg of modified nano-silica sol and 0.5 kg of deionized water, and wet-mixed for 180 seconds to obtain a mixed slurry. The mixed slurry is injected into a mold, vibrated to form the shape, and cured in the mold at 25°C for 48 hours before being demolded to obtain the blank. The billet is dried at 110℃ for 24 hours, then heated to 1100℃ at a rate of 3℃ / min and held for 3 hours in air, and then heated to 1650℃ at a rate of 5℃ / min and held for 3 hours to obtain a low-carbon and environmentally friendly refractory castable based on nano-sol.

[0051] Control group 2 The low-carbon, environmentally friendly refractory castable based on nanosol in this control group consists of the following components: ZrO2 hollow microspheres, modified nano-silica sol, dense corundum, brown corundum, white corundum, bauxite, silicon carbide, activated alumina, and spherical asphalt.

[0052] The preparation method of ZrO2 hollow microspheres in this control group includes the following steps: 60g of sucrose was dispersed in 500mL of deionized water and hydrothermally reacted at 170℃ for 8 hours. After naturally cooling to room temperature, the precipitate was collected, washed successively with deionized water and anhydrous ethanol, dried at 80℃, and then added to 50mL of hydrogen peroxide. The mixture was stirred at 60℃ for 2 hours, filtered, and the precipitate was collected. It was washed with deionized water until neutral and then vacuum dried at 80℃ to obtain carbon sphere templates. 50g of carbon sphere template and 25g of zirconium oxychloride octahydrate were dispersed in 500mL of deionized water. Then, a 1mol / L ammonia solution was slowly added dropwise to adjust the pH to 5.5. The reaction was continued with stirring for 2 hours. The precipitate was collected by centrifugation, washed with anhydrous ethanol until neutral, dried under vacuum at 80℃, and then heated to 300℃ at a rate of 3℃ / min and held for 1 hour in air. The temperature was then increased to 600℃ at a rate of 5℃ / min and held for 4 hours. After naturally cooling to room temperature, ZrO2 hollow microspheres were obtained.

[0053] The preparation method of the modified nano-silica sol in this control group includes the following steps: Weigh 50g of KH-570 and dissolve it in 500mL of anhydrous ethanol. Stir well to obtain KH-570 solution. After mixing 5 kg of silica sol and 5 kg of deionized water evenly, add KH-570 solution and heat to 50℃ and stir for 2 hours to obtain modified nano silica sol.

[0054] The preparation method of the low-carbon and environmentally friendly refractory castable based on nano-sol in this control group includes the following steps: Weigh out 0.8 kg of ZrO2 hollow microspheres, 1.2 kg of dense corundum (composed of 0.6 kg of dense corundum with a particle size of 5-8 mm and 0.6 kg of dense corundum with a particle size of 3-5 mm), 2.2 kg of brown corundum (composed of 1.1 kg of brown corundum with a particle size of 1-3 mm and 1.1 kg of brown corundum with a particle size of 0-1 mm), 1.4 kg of white corundum with a particle size of 325 mesh, and 1.8 kg of bauxite (composed of 1.1 kg of bauxite with a particle size of 3-5 mm). The mixture consists of 0.7 kg of 1-3 mm alumina and 0.6 kg of 325 mesh silicon carbide, 0.8 kg of activated alumina, and 0.5 kg of spherical asphalt. It is premixed for 100 seconds, then dry-mixed for 60 seconds, followed by the addition of 1.2 kg of modified nano-silica sol and 0.5 kg of deionized water. The mixture is then wet-mixed for 180 seconds to obtain the mixed slurry. The mixed slurry is injected into a mold, vibrated to form the shape, and cured in the mold at 25°C for 48 hours before being demolded to obtain the blank. The billet is dried at 110℃ for 24 hours, then heated to 1100℃ at a rate of 3℃ / min and held for 3 hours in air, and then heated to 1650℃ at a rate of 5℃ / min and held for 3 hours to obtain a low-carbon and environmentally friendly refractory castable based on nano-sol.

[0055] Performance testing 1. Flexural strength at room temperature: According to the national standard GB / T3001-2017, the room temperature flexural strength of the specimens was tested.

[0056] 2. Compressive strength at room temperature: The compressive strength of the specimen at room temperature was measured according to the national standard GB / T5072-2008.

[0057] 3. Thermal shock resistance: According to the national standard GB / T30873-2014, the thermal shock resistance of the specimens was tested. A water-cooling method was used, with three cycles, and the residual flexural strength retention rate of the specimens was used to characterize the thermal shock resistance of the castable.

[0058] Table 1. Performance test results of refractory castables in Examples 1-3 and Control Groups 1-2 Analysis of Examples 1-3 and Control Groups 1-2, combined with Table 1, shows that the low-carbon environmentally friendly refractory castable with added composite aerogel powder exhibits both excellent mechanical properties and thermal shock resistance. In Control Group 1, the low-carbon environmentally friendly refractory castable prepared in Control Group 2 did not contain ZrO2 hollow microspheres in the composite aerogel powder, resulting in insufficient internal support of the composite aerogel powder and poor rigidity. Compared to Examples 1-3, the low-carbon environmentally friendly refractory castable prepared in Control Group 2 did not contain composite aerogel powder, and the sample lacked thermal insulation voids. Thermal stress acted directly on the base material, reducing the flexural strength retention rate and resulting in insufficient durability and thermal shock resistance of the sample.

[0059] Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A low-carbon, environmentally friendly refractory castable based on nano-sol, characterized in that, It comprises the following components: composite aerogel powder, modified nano silica sol, dense corundum, brown corundum, white corundum, bauxite, silicon carbide, activated alumina, and spherical asphalt; the composite aerogel powder is made from SiO2, halloysite, and ZrO2 hollow microspheres.

2. The low-carbon, environmentally friendly refractory castable based on nano-sol according to claim 1, characterized in that: The preparation method of the composite aerogel powder includes the following steps: Tetraethyl orthosilicate and citric acid were dispersed evenly in anhydrous ethanol, then deionized water was added, the mixture was heated and stirred, halloysite and ZrO2 hollow microspheres were added, and after stirring evenly, ammonia water was added dropwise. The mixture was then sealed and allowed to stand to form a composite gel. Discard the upper layer of the composite gel, add anhydrous ethanol for aging, freeze-dry the composite gel after aging, grind and sieve it, and collect the sieve material to obtain the composite aerogel powder.

3. The low-carbon, environmentally friendly refractory castable based on nano-sol according to claim 2, characterized in that: The mass ratio of the ZrO2 hollow microspheres to halloysite is (0-2):

1.

4. The low-carbon and environmentally friendly refractory castable based on nano-sol according to claim 2, characterized in that: The preparation method of the ZrO2 hollow microspheres includes the following steps: Sucrose was dispersed in deionized water, and after hydrothermal reaction, the precipitate was collected, washed, and dried under vacuum. The precipitate was then added to hydrogen peroxide for reaction, and the precipitate was collected, washed, and dried under vacuum to obtain carbon sphere templates. Carbon sphere templates and zirconium oxychloride octahydrate were dispersed in deionized water, and then ammonia solution was added dropwise to adjust the pH. The reaction was stirred, the precipitate was collected, washed, dried under vacuum, calcined at high temperature, and cooled to obtain ZrO2 hollow microspheres.

5. The low-carbon, environmentally friendly refractory castable based on nano-sol according to claim 4, characterized in that: When adjusting the pH by adding ammonia solution, the pH range is 5-5.

5.

6. The low-carbon, environmentally friendly refractory castable based on nano-sol according to claim 1, characterized in that: The preparation method of the modified nano-silica sol includes the following steps: KH-570 was dispersed in anhydrous ethanol to obtain a KH-570 solution; after the silica sol and deionized water were mixed evenly, the KH-570 solution was added and the mixture was heated to react, thus obtaining the modified nano silica sol.

7. A preparation process for a low-carbon, environmentally friendly refractory castable based on nano-sol, characterized in that, Includes the following steps: Weigh out composite aerogel powder, dense corundum, brown corundum, white corundum, bauxite, silicon carbide, activated alumina, and spherical asphalt. Mix and stir, then add modified nano silica sol and deionized water, and wet mix to obtain a mixed slurry. The mixed slurry is injected into a mold to form a shape, cured in the mold, and then demolded to obtain a blank. The billet is dried and then calcined at high temperature to obtain a low-carbon and environmentally friendly refractory castable based on nano-sol.

8. The preparation process of a low-carbon and environmentally friendly refractory castable based on nano-sol according to claim 7, characterized in that: The mixing process involves premixing for 60-100 seconds, followed by dry mixing for 45-60 seconds.

9. The preparation process of a low-carbon and environmentally friendly refractory castable based on nano-sol according to claim 7, characterized in that: The curing time for the mold is 24-72 hours.

10. The preparation process of a low-carbon, environmentally friendly refractory castable based on nanosol according to claim 7, characterized in that: The high-temperature calcination involves heating to 1000℃-1200℃ at a rate of 3℃ / min and holding for 2-4 hours, followed by heating to 1500℃-1900℃ at a rate of 5℃ / min and holding for 2-4 hours.

Citation Information

Patent Citations

  • Silica sol and corundum combined castable and preparing method thereof

    CN105218113A

  • Heat-insulating refractory castable and preparation method thereof

    CN118324499A